Saúde mental e qualidade de vida de pacientes com migrânea durante a pandemia de Covid-19 - Thaís Brito Vilela (2023)
During the pandemic of Covid-19 (CONSONNI et al., 2021), the abrupt self-isolation and the social reorganization were significant factors for psychological suffering. Having this context in mind, people who suffer from migraine needed to change the management of their treatment sue to rescheduling, postponement and cancellation of appointments, as well as psychotherapy sessions and many other urgent readaptations due to social distancing. Objective: verify the subjective evaluation concerning the negative impact of the pandemic and measurements of life quality, anxiety, depression, and incapability of patients with migraine, weather it is chronicle or episodic, when compared to another control group. Method: this is a transversal, descriptive, retrospective, and quantitative study, with samplesfrom 113 people divided between the control groups (C), the patients with chronicle migraine (CM) and the patients with episodic migraine (EM). Results: women are the majority in all three study groups, with a proportion of 80% or more. Approximately, 90% of samples from the CM group presents symptoms followed by phonophobia and photophobia, which are features of such syndrome. Besides, we’ve observed that the group CM presents a higher average in the subcategories total functional impact and daily frequency, when compared to the average values of the group EM. It is important to highlight that the control group CM presented higher values in all categories in the dimension of life quality during the pandemic and the group EM reported less social and pain impact, when compared to the group of CM. Conclusion: there was an increasing complaint of pain days, for a bigger picture besides worldwide and sanitary scenarios, as well as physical limitations which can be associated with the development of mood disorders (HEADACHE SOCIETY, 2018). Thus, we suggest a stronger guidance of patients with Chronicle migraine as far as the need of treating the cause and the management of an environment and of followed symptoms, with the goal of decreasing pain, suffering and incapability. On the other hand, patients with episodic migraine should be guided as far as impacts related to social stress, which may cause symptoms that bring them closer to the severity of the chronical condition.